2001
DOI: 10.1152/physiologyonline.2001.16.4.152
|View full text |Cite
|
Sign up to set email alerts
|

The Intrarenal Endothelin System and Hypertension

Abstract: The kidney is both a source of endothelin (ET) generation and an important target organ of this peptide. The highest concentrations of ET-1 in the body exist in the renal medulla, where it mediates natriuretic and diuretic effects through the ET(B) receptor subtype. It is proposed that aberrations in the renal ET system may lead to sodium and water retention and subsequently to the development of hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 14 publications
3
33
1
Order By: Relevance
“…The findings of the present study suggest that the renal ET-1 system may likewise participate in the regulation of sodium excretion in response to high salt intake. This lends further support to the notion that ET-1 synthesized in the renal medulla may act locally as a natriuretic factor and participates in the regulation of salt and water homeostasis [9, 10, 14, 15]. In particular, this may be of importance in situations of increased dietary salt intake or in pathophysiological circumstances associated with the development of positive sodium balance [18].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The findings of the present study suggest that the renal ET-1 system may likewise participate in the regulation of sodium excretion in response to high salt intake. This lends further support to the notion that ET-1 synthesized in the renal medulla may act locally as a natriuretic factor and participates in the regulation of salt and water homeostasis [9, 10, 14, 15]. In particular, this may be of importance in situations of increased dietary salt intake or in pathophysiological circumstances associated with the development of positive sodium balance [18].…”
Section: Discussionsupporting
confidence: 64%
“…Previously, several studies addressed the importance of the ET-1 system in the regulation of sodium excretion by the kidney [9, 10]. Thus, it has been demonstrated that ET-1 exerts a direct tubular natriuretic action that is mediated by the ET B receptor subtype [9, 11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…The actions of ET-1 in the cortex may contribute to the decline in renal function and exaggerated hypertension observed during ANG II and HS treatment. The increased cortical immunoreactive ET levels seen during combined HS and ANG II treatment may cause vasoconstriction of the cortical vasculature via ET A receptors and reduction in cortical blood flow (1,14). ET A -receptor blockade reduces the rise in MAP and decline in glomerular filtration rate associated with ANG II-induced hypertension (2)(3)(4)18), indicating an important role for ET-1 in mediating the renal hemodynamic response via ET A receptors during ANG II-induced hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide (NO) augments salt and water excretion by the kidney (1)(2)(3)(4)(5)(6). NO produced by both NOS1 and NOS3 (neuronal and endothelial NOS 2 ) contributes to this effect (7)(8)(9).…”
mentioning
confidence: 99%